Gestão integrada da doença renal crónica: análise de uma política inovadora em Portugal - Coelho, Anabela (2014)
The implementation in Portugal of a model for integrated management of disease applied to the end-stage renal disease, from 2008 onwards, has completely restructured the way of providing care, as well as the payment and follow-up of patients under dialysis. This article describes the steps taken by the Ministry of Health, in terms of the planning, implementation and follow-up of the policy, with a particular focus on the importance of involving the various groups of interest, the leadership, as well as the capacity of negotiation and influence of the Government.